A new continuous system of enzymatic hydrolysis coupled with membrane separation for isolation of peptides with angiotensin I converting enzyme inhibitory capacity from defatted corn germ protein. Issue 1 (12th December 2019) - Musa, Abubakr; Gasmalla, Mohammed A. A.; Ma, Haile; Karrar, Emad; Sarpong, Frederick; Wali, Asif; Duan, Yuqing
Abstract : Production of peptides with Angiotensin I converting enzyme (ACE)-inhibitory capacity from ultrasonically pretreated defatted corn germ protein (DCGP) by using a new continuous system of enzymatic hydrolysis coupled with membrane separation (EHC-MS). Abstract : In this study, separation of peptides with Angiotensin I converting enzyme (ACE)-inhibitory capacity obtained from ultrasonically pretreated defatted corn germ protein (DCGP) by using a new continuous system of enzymatic hydrolysis coupled with membrane separation (EHC-MS) was investigated. Ultrasonic pretreatment was applied to enhance the enzymatic hydrolysis rate of DCGP, as proved in our previous study. The EHC-MS system was operated in two modes which included the batch system and continuous system with continuous water and substrate feeding and was compared with the EH-offline-MS system. The selection of the membrane was based on the hydrolysate fraction which had the highest activity for inhibition of ACE. The results showed that the 1–3 kDa fraction of DCGP hydrolysates had the lowest IC50 value (0.124 mg mL −1 ) for inhibition of ACE. The degree of conversion (%) of DCGP and output of peptides per unit of the enzyme were significantly ( P < 0.05) increased by 55.3% and 55% in the EHC-MS batch process and 79% and 473% in the EHC-MS continuous operation compared to the EH-offline-MS system. The EHC-MS using continuous water and substrate feeding operation was noted to be the best in terms of a high degree of DCG protein conversion (75.68 ± 1.34) and the output of peptides per unit of the enzyme (78.65 ± 1.13). The results revealed that the EHC-MS method with constant water and substrate feeding could show a better application in peptide production in the food industry.